Modulating BET Bromodomain Inhibitor ZEN‐3694 and Enzalutamide Combination Dosing in a Metastatic Prostate Cancer Patient Using CURATE.AI, an Artificial Intelligence Platform. Issue 6 (29th August 2018) - Pantuck, Allan J.; Lee, Dong‐Keun; Kee, Theodore; Wang, Peter; Lakhotia, Sanjay; Silverman, Michael H.; Mathis, Colleen; Drakaki, Alexandra; Belldegrun, Arie S.; Ho, Chih‐Ming; Ho, Dean
Abstract: Combination chemotherapy is a cornerstone of cancer treatment. Optimizing its effectiveness requires dose‐ and time‐dependent regulation of drug synergy. In this report, CURATE.AI, an artificial intelligence platform, is used to prospectively guide the dosing of a bromodomain inhibitor (ZEN‐3694) and enzalutamide administered in combination to a patient with metastatic castration‐resistant prostate cancer to reduce serum prostate‐specific antigen (PSA) levels. CURATE.AI successfully identifies substantial ZEN‐3694 and enzalutamide dose adjustments, increasing both treatment efficacy and tolerance. CURATE.AI analysis also confirms that the patient's durable response is mediated by ZEN‐3694 inclusion in the regimen. Due to CURATE.AI‐enhanced efficacy and safety, the patient was able to continue with the combination regimen, resulting in a durable response and no disease progression based on CURATE.AI‐sustained control over PSA levels and reduced lesion size. Abstract : In combination therapy, drug synergy is dose‐dependent, time‐dependent, and patient‐specific. To address these challenges, CURATE.AI, a powerful artificial intelligence platform is used to guide BET bromodomain inhibitor ZEN‐3694 and enzalutamide dosing in a metastatic prostate cancer patient. Following CURATE.AI implementation, a durable response and no apparent disease progression are observed in the patient.